Cave People? Cave Tourists? Explorers? Going Underground in the Eyes of Representatives of the Cavers’ Community - Chylińska Dagmara (Quaestiones Geographicae)
Cave tourism is a phenomenon most frequently studied in the context of the potential for other forms of tourism (including geotourism, archeotourism, ecotourism) and the impact of tourism on the cave environment. Motivational research among tourists is market-oriented and usually conducted in so-called ‘show caves’ (adapted for tourism and regularly opened to the public). In the context of social research in caves, the author of the paper notices a research gap: cave tourism also happens in caves that are inaccessible to everyone due to the degree of difficulty of exploration and the lack of necessary skills. The research on a group of 57 members of Polish caving clubs was aimed at studying this community in terms of motivation, perception of the activity practiced (benefits, costs, risks, overall tourist phenomena), and self-definition, the identity of the group. Taking into account the limitations of inference due to the size of the sample, the prospective directions of research on the community of tourists and explorers eluding previous studies of cave tourism were established.